Characterizing aquatic habitats for long‐term monitoring of a fourth‐order, regulated river in the Pacific Northwest, USA. (30th November 2017) - Konrad, C.P.; Burton, K.; Little, R.; Gendaszek, A.D.; Munn, M.D.; Anderson, S.W.
Abstract: A pragmatic approach to the long‐term monitoring of rivers leverages available information with targeted field investigations to address key uncertainties relevant to management decisions. An over‐arching management issue for many rivers is how reservoir operation affects the amount and location of in‐channel sediment and the resulting distribution of aquatic habitats. We integrate remotely acquired and field‐survey morphologic data for the Cedar River, Washington, to constitute the current status of aquatic habitats and benchmarks for long‐term monitoring that will inform streamflow management. Four key habitats (river edge, side channels, riffles, and pools) are feasible to monitor with high‐resolution aerial imagery, a longitudinal profile of the river, and a side channel inventory, but full characterization of the functional differences within these habitats requires additional information. Habitat use information such as redd surveys will continue to be important for long‐term monitoring where it cannot be inferred reliably from physical habitat characteristics.